2020
DOI: 10.1186/s13568-020-01059-7
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Anguilla marmorata population in Thua Thien Hue, Vietnam based on the cytochrome C oxidase I (COI) gene fragments

Abstract: The giant mottled eel is a species with high commercial value so overfishing, river management, and water pollution have negatively affected its movement and population numbers. Anguilla marmorata (eel) was listed in the Vietnam Red Data Book 2007 with a description of Vulnerability. This study used a barcode technique to analyze molecular characteristics and build genetic plants based on the cytochrome c oxidase I gene segment isolated from the mitochondrial genome of 48 individuals of A. marmorata collected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The molecular phylogenetic tree and the haplotype network of A. marmorata in Malaysia, Thailand and Vietnam suggested that the eel might be transported from the Western North Pacific spawning area and propose possible dispersion and migration of A. marmorata into Southeast Asian waters. In Thua Thien Hue province, DNA barcode techniques used to analyze molecular characteristics and build phylogenetic based on the COI segment showed that separation of the A. marmorata population is guided by the migration process and specific ecological parameters (Huyen and Linh, 2020) and their genetic evolution occurs in the direction of random population expansion (Linh and .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular phylogenetic tree and the haplotype network of A. marmorata in Malaysia, Thailand and Vietnam suggested that the eel might be transported from the Western North Pacific spawning area and propose possible dispersion and migration of A. marmorata into Southeast Asian waters. In Thua Thien Hue province, DNA barcode techniques used to analyze molecular characteristics and build phylogenetic based on the COI segment showed that separation of the A. marmorata population is guided by the migration process and specific ecological parameters (Huyen and Linh, 2020) and their genetic evolution occurs in the direction of random population expansion (Linh and .…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction and sequence analysis Total genomic DNA was extracted by the method descriped by Kumar et al (2007) with a modification. The PCRs were carried out using two primer pairs: A.marFw-1-5'GCACTAAGCTTCTAATCCG3' and A.marRv-1-5' GATGATTATTGTGGCAGAAG3' (Huyen and Linh, 2020) for amplification of the COI gene; L2510 (5′CGC CTG TTT ATC AAA AAC AT3′) and H3080 (5′CCG GTC TGA ACT CAG ATC ACG T3′) (Palumbi et al, 1991) for amplification of 16S rRNA gene. The amplification reactions were performed in a total volume of 35 μL.…”
Section: Morphological Analysismentioning
confidence: 99%
“…This induces then isolation by time (IBT) of spawning groups. individuals in eel populations in Thua Thien Hue and it was divided into two separate groups that are guided by the migration process and speci c ecological (Huyen and Linh 2020).…”
Section: Discussionmentioning
confidence: 99%
“…IBT causes a restriction in gene ow, taking place between early and late spawners (Hendry and Day 2005). And the last, based on analyzed three different phylogenetic trees of A. marmorata population in Thua Thien Hue, Vietnam, Huyen and Linh (2020) showed that there was the high genetic similarity of individuals in eel populations in Thua Thien Hue and it was divided into two separate groups that are guided by the migration process and speci c ecological (Huyen and Linh 2020).…”
Section: Discussionmentioning
confidence: 99%